2018
DOI: 10.12659/pjr.900071
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Imaging of Pregnant Women – The Role of Magnetic Resonance Imaging

Abstract: SummaryBackgroundPresentation of magnetic resonance imaging (MRI) findings in pregnant women in the Department of Diagnostic Imaging, Institute of Mother and Child, Warsaw, Poland.Material/MethodsForty-three symptomatic pregnant women underwent MRI between 9 and 33 weeks of gestation (mean of 23 weeks). Moreover, we included 2 pregnant women who underwent fetal MRI and had incidental abnormalities.ResultsIn 9 cases, we excluded the suspected brain abnormalities. In 4 cases, we found unremarkable changes in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Modern MRI devices enable not only accurate and reliable assessment of renal artery stenosis, but also facilitate diagnosis of many other pathologies (e.g. pheochromocytoma) even with non-contrast-enhanced scans [34,35].…”
Section: Safety Of Radiographic Imaging In Pregnancymentioning
confidence: 99%
“…Modern MRI devices enable not only accurate and reliable assessment of renal artery stenosis, but also facilitate diagnosis of many other pathologies (e.g. pheochromocytoma) even with non-contrast-enhanced scans [34,35].…”
Section: Safety Of Radiographic Imaging In Pregnancymentioning
confidence: 99%
“…CT, being more accessible, is more frequently utilized compared to MRI. However, in pregnant patients, MRI is preferred due to its avoidance of high-contrast resolution and radiation exposure to the fetus in comparison to CT [ 11 ]. In the presented case, the patient did not have hypercalcemia on her pathology tests; however, notable findings included elevated CA 125 levels and the presence of a prominent likely ovarian mass with ascites appreciated on both ultrasound and MRI.…”
Section: Discussionmentioning
confidence: 99%
“…But use of the MRI contrast agent gadolinium is discouraged as it crosses the placenta and is excreted into the amniotic fluid. [ 20 ] A study by Bekiesińska-Figatowska et al [ 21 ] of about 43 symptomatic pregnant women between 9 and 33 weeks’ gestation who required an imaging work-up suggested that MRI is the best imaging modality for pregnant women when US is inconclusive, when masses are too large to fully assess with US, or when there is a high risk of malignancy. Pregnancy affects growth invasion and metastasis in ovarian cancer, and ovarian cancer increases various maternal and fetal complications.…”
Section: Discussionmentioning
confidence: 99%